Life of thermal bubble on platinum microheater - Kim, Ho-Young; Jeong, Kwang-Hun; Ko, Seunghyun; Lee, Heon Ju; Lee, Yoon Pyo; Chang, Young Soo (AMER INST PHYSICS, 2007)
When electrical current is supplied to a microline heater immersed in liquid, a microthermal bubble can be formed. The bubble grows until it becomes too large to adhere to a solid surface and finally departs into liquid completing its life. Here we report the experimental results associated with the life of a thermal bubble continuously heated by a platinum microheater. We investigated the effects of the heater dimensions on the nucleation temperature. It was found that a bubble nucleates at lower temperature as the heater gets wider. We also measured the departure diameter and frequency of thermal bubbles depending on the thermal conditions of the microheater and the ambient liquid. As the microheater temperature increases, both the departure diameter and frequency increase, showing different behaviors from those of macroscale boiling. However, as the ambient liquid temperature rises, the departure diameter decreases despite the increase of the departure frequency. Finally, the transient temperature profile of the microheater during bubble formation process was measured. Rapid drop and rise of the temperature were observed, which are attributed to the small-scale convection of cold ambient liquid. (c) 2007 American Institute of Physics.
Keywords: NUCLEATION